Hematopoietic Stem and Progenitor Cells in Inflammation and Allergy - Fischer, Kimberly D.; Agrawal, Devendra K. (Frontiers in Immunology, 2013)
Hematopoietic stem and progenitor cells contribute to allergic inflammation. Pro-inflammatory cytokines that are generated following allergen challenge can impact the differentiation of hematopoietic progenitor cells leading to increased production of effector cells such as eosinophils and basophils, which are key cells involved in the pathogenesis of allergic airway inflammation. Homing of stem cells to the lungs is associated with inflammatory and remodeling changes in asthmatics. Factors that modulate the differentiation and increased migration of stem cells to the site of inflammation in asthma remain to be defined. Stem cells can mature at the site of inflammation in response to inflammatory mediators and other components in the milieu. While the available data suggest that hematopoietic cells traffic to target tissues, the molecular factors underlying in situ differentiation have yet to be specified. Here, we critically evaluate the potential role of hematopoietic progenitors in contributing to the increased immune cell infiltrate in allergic asthma and the factors that drive their differentiation.